2007
DOI: 10.1113/jphysiol.2007.130062
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility for homeostatic plasticity is down‐regulated in parallel with maturation of the rat hippocampal synaptic circuitry

Abstract: Homeostatic regulation, i.e. the ability of neurons and neuronal networks to adjust their output in response to chronic alterations in electrical activity is a prerequisite for the pronounced functional plasticity in the developing brain. Cellular mechanisms of homeostatic plasticity have mainly been studied in cultured preparations. To understand the developmental time frame and properties of homeostatic plasticity under more physiological conditions, we have here compared the effects of activity deprivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In contrast, blockade of synaptic activity in developing hippocampal neurons does not appear to modify the number of cell surface GABA A Rs or their accumulation at synaptic sites (Harms and Craig, 2005). This discrepancy may reflect the varying ages of the culture preparations used (Huupponen et al, 2007) or the length of activity blockade, 24 h compared with 18 d. Intriguingly, it has been demonstrated recently that exposure of cultured neurons to TTX over a period of 7-14 d results in retraction of dendrites and a loss of spines (Fishbein and Segal, 2007). Therefore, this phenomenon may complicate the analysis of the long-term effects of activity blockade on the formation of inhibitory synapses.…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, blockade of synaptic activity in developing hippocampal neurons does not appear to modify the number of cell surface GABA A Rs or their accumulation at synaptic sites (Harms and Craig, 2005). This discrepancy may reflect the varying ages of the culture preparations used (Huupponen et al, 2007) or the length of activity blockade, 24 h compared with 18 d. Intriguingly, it has been demonstrated recently that exposure of cultured neurons to TTX over a period of 7-14 d results in retraction of dendrites and a loss of spines (Fishbein and Segal, 2007). Therefore, this phenomenon may complicate the analysis of the long-term effects of activity blockade on the formation of inhibitory synapses.…”
Section: Discussionmentioning
confidence: 59%
“…For example, in the rat hippocampus, a period of in vivo activity blockade by TTX application results in scaling-up of pyramidal neuron mEPSC amplitudes in juvenile animals, but has no effect on mEPSC amplitude in adults (18), whereas the susceptibility to TTX incubation-induced scaling-up of mEPSC amplitude declines significantly between P4 and P8 (17). Interestingly, a nonmultiplicative form of DE-induced synaptic plasticity, which comprises a nonuniform increase in synaptic weights, has been reported to persist into adulthood in L2/3 of the mouse visual cortex (16).…”
Section: Discussionmentioning
confidence: 99%
“…One study has suggested that a form of synaptic scaling persists into adulthood in layer 2/3 (L2/3) of the visual cortex (16). On the other hand, studies in the hippocampus have shown that homeostatic plasticity, and synaptic scaling in particular, are down-regulated during development (17,18).…”
mentioning
confidence: 99%
“…Since interneurons are the key players in setting the temporal coherence critical for synaptic plasticity and neuronal network oscillations, a mechanism that could switch the interneuronal firing pattern from "newborn" to "adult" type would have a privileged role in the activitydependent maturation of the brain. There are several reports demonstrating the critical role of early hippocampal network bursts in guiding synaptic maturation (Lauri et al, 2003;Huupponen et al, 2007) and the instrumental role of interneurons in synchronizing this activity Palva et al, 2000, Ben-Ari et al 2004). Thus, our findings disclose a critical endogenous mechanism controlling the level of interneuronal output during development that can be of vital importance in the development of functional synaptic circuits in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%